2012
DOI: 10.1111/j.1559-1816.2012.00982.x
|View full text |Cite
|
Sign up to set email alerts
|

The Big Five Personality Factors and Mass Politics

Abstract: In this paper, we argue that a stable set of characteristics—personality—can help explain mass political opinions and behavior. By analyzing data collected from over 750 people, we examine the influence of the Five‐Factor Model of personality on ideology, partisanship, political efficacy, and two forms of political participation. After controlling for a host of demographic factors, we find that openness to experience, agreeableness, conscientiousness, and extraversion help explain public opinion and political … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
68
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 43 publications
8
68
0
1
Order By: Relevance
“…Conservatives are found to have higher levels neuroticism (called by its inverse, emotional stability, in the current study here on relationships; Van Hiel et al, 2007). Sweetser (2014) points out that the literature in this area shows agreement among scholars that Liberals and Conservatives differ on openness to experiences (Liberals high, Conservatives low) and conscientiousness (Liberals low, Conservatives high) (Cooper et al, 2013;Ha, Kim, & Jo, 2013;Van Heil & Mervielde, 2004). To this point, Cooper et al (2013) concluded findings regarding partisan personality for extraversion, agreeableness, and emotional stability necessitate more research to more accurately build a personality profile.…”
Section: Personality and Politicssupporting
confidence: 50%
See 3 more Smart Citations
“…Conservatives are found to have higher levels neuroticism (called by its inverse, emotional stability, in the current study here on relationships; Van Hiel et al, 2007). Sweetser (2014) points out that the literature in this area shows agreement among scholars that Liberals and Conservatives differ on openness to experiences (Liberals high, Conservatives low) and conscientiousness (Liberals low, Conservatives high) (Cooper et al, 2013;Ha, Kim, & Jo, 2013;Van Heil & Mervielde, 2004). To this point, Cooper et al (2013) concluded findings regarding partisan personality for extraversion, agreeableness, and emotional stability necessitate more research to more accurately build a personality profile.…”
Section: Personality and Politicssupporting
confidence: 50%
“…Sweetser (2014) points out that the literature in this area shows agreement among scholars that Liberals and Conservatives differ on openness to experiences (Liberals high, Conservatives low) and conscientiousness (Liberals low, Conservatives high) (Cooper et al, 2013;Ha, Kim, & Jo, 2013;Van Heil & Mervielde, 2004). To this point, Cooper et al (2013) concluded findings regarding partisan personality for extraversion, agreeableness, and emotional stability necessitate more research to more accurately build a personality profile. As such, there a there is still much debate about the finer points of ideology and personality.…”
Section: Personality and Politicsmentioning
confidence: 96%
See 2 more Smart Citations
“…The newly generated personality measures are short -yet reliable -enough to be incorporated in large-scale surveys. They eventually lead to a growing number of studies that report a direct, significant effect of personality on political ideology (e.g., Carney, Jost, Gosling, & Potter, 2008;Gerber et al, 2010), party identification (e.g., Gerber, Huber, Doherty, & Dowling, 2012a;Vecchione et al, 2011), political efficacy (e.g., Cooper, Golden, & Socha, 2013), political discussion (e.g., Gerber, Huber, Doherty, & Dowling, 2012b;Hibbing, Ritchie, & Anderson, 2011), vote choice (e.g., Barbaranelli, Caprara, Vecchione, & Fraley, 2007;Schoen & Schumann, 2007), voter turnout (e.g., Gerber et al, 2011;Mattila et al, 2011), and non-electoral political participation (e.g., Gallego & Obserski, 2011;Mondak, Hibbing, Canache, Selig-son, & Anderson, 2010). It is also known that personality traits exert a direct influence on citizens' opinion on a specific political issue such as the usage of military force in foreign affairs (Schoen, 2007) and immigration (Vecchione, Caprara, Schoen, Castro, & Schwartz, 2012).…”
mentioning
confidence: 99%